survay of Mothers\' Behavior and Perceptions of Benefits and barriers in Preparing healthy breakfast and snacks for school children - Sakineh Rakhshanderou; Mohtasham Ghaffari; ameneh pooresmaeildorosteh (آموزش بهداشت و ارتقاء سلامت ایران, 2020)
Background and Objective: Healthy breakfast and snacks have important role to student thought and body health. The aim of this study was to survey the Behavior And perceptions of mothers about the benefits and barriers of preparation of healthy breakfast and snacks for school children.